The pediatric microbiome and the lung. Issue 3 (June 2015) - Tracy, Michael; Cogen, Jonathan; Hoffman, Lucas R.
<x xml:space="preserve">Abstract</x> Purpose of review Many pediatric lung diseases are characterized by infection. These infections are generally diagnosed, studied, and treated using standard culture methods to identify 'traditional pathogens'. Based on these techniques, healthy lungs have generally been thought to be sterile. However, recent advances in culture-independent microbiological techniques challenged this paradigm by identifying diverse microbes in respiratory specimens (respiratory microbiomes) from both healthy people and those with diverse lung diseases. In addition, growing evidence suggests a link between gastrointestinal microbiomes and inflammatory diseases of various mucosal surfaces, including airways. Recent findings This article reviews the rapidly developing field of respiratory microbiome research, emphasizing recent progress made employing increasingly sophisticated technologies. Although many of the relevant studies have focused on adults with cystic fibrosis, recent research has included children and adults with other respiratory diseases, as well as healthy individuals. These studies suggest that even healthy children have airway microbiomes, and that both respiratory and gastrointestinal microbiomes often differ between healthy people and those with different types and severities of airway disease. The causal relationships between microbiomes, disease type and progression, and treatments such as antibiotics must now be defined. Summary The advent of culture-independent microbiological techniques has transformed how we think about the relationship between microbes and airway disease. More research is required to translate these findings to improved therapies and preventive strategies.